1960
DOI: 10.1080/00288233.1960.10418090
|View full text |Cite
|
Sign up to set email alerts
|

French-bean rust (Uromyces appendiculatus) studies on resistance and determination of rust races present in New Zealand

Abstract: The probable races of bean rust present in New Zealand are 10, 17, and 28, as identified in United States of America, with possibly another unidentified race which attacks the differential line "U.S. 780".In crosses of the resistant variety Westralia with susceptible varieties, heterozygote plants show a delayed, but definite infection with rust in field and glasshouse trials. Homozygous susceptible plants show equal susceptibility with susceptible parents. Susceptibility can thus be termed recessive or domina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

1965
1965
2010
2010

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The Harter and Zaumeyer set of seven differentials and various other smaller sets were used to characterize races in the United States Fisher 1952), Brazil (de Menezes 1952Dias and Da Costa 1968;Netto et al 1969;Ferraz 1969 in Coelho and Chaves 1975;Augustin and Da Costa 1971;Coelho and Chaves 1975;Carrijo et al 1980), Colombia (Zú ñ iga de Rodriguez and Victoria 1975), Mexico (Crispen, in Crispen and Dongo 1962;Crispen and Dongo 1962), Peru (Guerra and Dongo 1973), Costa Rica (Christen and Echandi 1967), Puerto Rico (Ruiz et al 1982), Jamaica (Shaik 1985b), eastern Africa (Howland and Macartney 1966), Australia (Waterhouse 1954;Ogle and Johnson 1974;Ballantyne 1978), New Zealand (Yen and Brien 1960), and Europe (Portugal, Madeira and S. Tom e) (Rodrigues 1955). Several authors also reported one or two new races in their areas using these differentials (Weaver and Marcus 1949;Sappenfield 1954;Zaumeyer 1960;Groth and Shrum 1977;Hikida 1961;McMillan 1972).…”
Section: Race Characterizationmentioning
confidence: 99%
“…The Harter and Zaumeyer set of seven differentials and various other smaller sets were used to characterize races in the United States Fisher 1952), Brazil (de Menezes 1952Dias and Da Costa 1968;Netto et al 1969;Ferraz 1969 in Coelho and Chaves 1975;Augustin and Da Costa 1971;Coelho and Chaves 1975;Carrijo et al 1980), Colombia (Zú ñ iga de Rodriguez and Victoria 1975), Mexico (Crispen, in Crispen and Dongo 1962;Crispen and Dongo 1962), Peru (Guerra and Dongo 1973), Costa Rica (Christen and Echandi 1967), Puerto Rico (Ruiz et al 1982), Jamaica (Shaik 1985b), eastern Africa (Howland and Macartney 1966), Australia (Waterhouse 1954;Ogle and Johnson 1974;Ballantyne 1978), New Zealand (Yen and Brien 1960), and Europe (Portugal, Madeira and S. Tom e) (Rodrigues 1955). Several authors also reported one or two new races in their areas using these differentials (Weaver and Marcus 1949;Sappenfield 1954;Zaumeyer 1960;Groth and Shrum 1977;Hikida 1961;McMillan 1972).…”
Section: Race Characterizationmentioning
confidence: 99%
“…198 3: Stavely and Pastor-Corrales, 1989). Dean rust races have also bee11 identified in Australasia (Waterhouse, 195 3: Yen andRrien, 1960: Ogle andJohnson, 1974;Ballantyne, 1978), Europe (Hubbeling, 1957: Allen, I9 75a), Asia (Yeh, 1983) and Africa ( IIowland and Macartney, 1966;Allen, 1975a: Mrnbaga andStavely, 1988). As many as eight races may be found among collections from a single field of a susceptible cultivar (Stavely, 1984b), and changes in virulence gene frequencies occur (Augustin at (11.. 1972: Alexander et al.…”
Section: Biologymentioning
confidence: 99%
“…ções prevalecentes no campo (YEN, 1960;AUGUSTIN et alii, 1972;HERNAJvDEZ BRAVO e CALVEZ, 1976;RIBEIRO, 1977;RIVERA, 1977;CARVALHO et alii,1978a;1978b).…”
Section: Observações Realizadas Emunclassified